2018
DOI: 10.1177/0001839218782131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Accelerator Designs in Mitigating Bounded Rationality in New Ventures

Abstract: Using a nested multiple-case study of participating ventures, directors, and mentors of eight of the original U.S. accelerators, we explore how accelerators' program designs influence new ventures' ability to access, interpret, and process the external information needed to survive and grow. Through our inductive process, we illuminate the bounded-rationality challenges that may plague all ventures and entrepreneurs-not just those in accelerators-and identify the particular organizational designs that accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
207
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 136 publications
(208 reference statements)
4
207
1
1
Order By: Relevance
“…Our literature review reported a lack of agreement on whether between accelerator differences explain differences in venture performance (Cohen & Hochberg, 2014). Hallen, Bingham, and Cohen et al (2019) compared accelerated ventures against nonaccelerated ventures and found that top accelerator programs shortened the time for raising capital, accelerating sales, and shortening the time to exit. They did not find evidence that accelerators influenced start‐up development activity, such as the hiring and training of talent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our literature review reported a lack of agreement on whether between accelerator differences explain differences in venture performance (Cohen & Hochberg, 2014). Hallen, Bingham, and Cohen et al (2019) compared accelerated ventures against nonaccelerated ventures and found that top accelerator programs shortened the time for raising capital, accelerating sales, and shortening the time to exit. They did not find evidence that accelerators influenced start‐up development activity, such as the hiring and training of talent.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while the data are useful for our variance decomposition method, we lack detailed organizational and process information on accelerators or ventures. Though recent studies have showed that accelerators to play an important role in accelerating ventures on the path to commercialization (Cohen et al, 2019; Cohen & Hochberg, 2014; Hallen et al, 2019) and that sorting effects are controlled by “inverse probability of treatment weights calculated at the venture‐level to dampen the influence of any sorting dynamics based on observable attributes” (Hallen et al, 2019, p. 18), our results cannot say anything about whether and how a particular accelerator impacted a particular venture's performance. Instead, our methodology can only explain whether differences between accelerators explained differences in venture performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations